Media Literacy: A Survey among Headteachers of Community Schools in Kathmandu Valley - Dhital, Govinda (Bodhi: An Interdisciplinary Journal, 2023)
This study has aimed to measure the level of media literacy among headteachers of community schools in Nepal and examine the relationship between their communication behavior and their awareness of media literacy. The study focuses on the level of media literacy among headteachers and the contribution of headteachers' media literacy to their communication behavior. The study considers demographic variables such as gender, ethnicity, age, marital status, academic qualification, teaching experience, and training to achieve the expected outcomes. The population of this study includes 295 secondary-level headteachers of community schools in Kathmandu Valley, and a sample of 170 headteachers were randomly selected from three districts. The collected data were analyzed using inferential statistics, and reliability, validity, and ethics were considered at each stage of the research. The findings indicate that headteachers are not sufficiently aware of the influence of media on their jobs in general, but there is a positive relationship between media literacy and communication behavior among them. Female headteachers felt recognized and had good relationships with colleagues, while older headteachers were less literate about media. Headteachers with higher qualifications and training were more literate with media and more communicative with subordinates and students. The study suggests that headteachers should constructively engage in building their schools, develop a social network, and maintain autonomy in their decision-making process to support the quality improvement of community schools. Therefore, the study recommends that stakeholders of the school consider the knowledge development, autonomy, and media literacy of headteachers to improve communication, collaboration, and quality of education in community schools.